(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the existing problems of distance learning of foreign languages ​​at a university from two sides: from the student’s point of view and from the teacher’s point of view. The article also attempts to suggest ways to solve emerging problems based on personal experiences of teaching and learning.